Kerentanan Ekonomi Masyarakat Pasca Bencana: Analisis Kebijakan Respons Darurat Pemerintah terhadap Aksi Penjarahan sebagai Strategi Bertahan Hidup di Indonesia - Sandy Kurniawan; Siti Nurhidayah (Journal of Public Administration and Local Governance, 2026)
This study investigates the economic vulnerability of post-disaster communities and analyzes the effectiveness of the Indonesian government’s emergency response policies in addressing such vulnerability while preventing looting as a form of survival strategy. Looting, within this context, is not merely seen as a criminal act but rather as a rational adaptive response to institutional failure particularly when aid distribution systems and social protection frameworks fail to meet urgent basic needs. Employing a Systematic Literature Review (SLR) guided by the PRISMA model, this research systematically reviewed and synthesized 87 peer-reviewed academic articles drawn from Scopus, DOAJ, and SINTA databases. Through thematic synthesis, four dominant themes emerged: (1) institutional and policy weaknesses, (2) socio-economic vulnerability, (3) adaptive survival behavior, and (4) community resilience. The results indicate that Indonesia’s emergency response policies remain reactive, fragmented, and inadequately integrated with the principles of Adaptive Social Protection (ASP). Conceptually, this study contributes to the interdisciplinary understanding of the relationship between public policy, social vulnerability, and behavioral adaptation in crisis situations. Practically, it calls for institutional reform and the design of community-based, socially just, and adaptive emergency response frameworks that strengthen Indonesia’s capacity to develop a more inclusive, responsive, and sustainable social protection system capable of reducing economic vulnerability and preventing social conflict in future disaster events.